A high-need Azeri school: A Georgian perspective. (July 2014) - Sharvashidze, Nino; Bryant, Miles
This article contributes to the International Study of Leadership Development Network initiative to identify high-need schools around the globe by focusing on a small minority ethnic school in the country of Georgia. It will be clear in this article that the challenges the Karajala School administrator faces in this former Soviet bloc school stand as an example of the educational disadvantages common to rural minority ethnic schools in Georgia and to many small rural schools in former Soviet bloc nations. The Karajala School is populated with Azeri students and is located in an isolated agrarian village. In the Republic of Georgia, both conditions are markers of a high-need school. The national Ministry of Education struggles to develop educational resources for the educators and students in these types of schools. School principals are woefully ill-prepared to implement modern reforms in education. Even with its new facility, modernized classrooms, indoor restrooms, and a central heating system, Karajala remains a high-need school. This article provides a portrait of this school, identifies the factors that make it a high-need school, links the properties of this type of school to matters of social justice, and identifies the challenges that this school must overcome to address expectations of educational quality and justice.